2020
DOI: 10.1177/0954008320913105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetylacetone metal salts on curing mechanism and thermal stability of polybenzoxazine

Abstract: To overcome high water absorption of inorganic metal salts and their poor compatibility with resin, acetylacetone metal salts (M(acac) n) were selected as the catalysts of benzoxazine resin. Their effects on the catalytic activity, structure, and thermal stability of polybenzoxazine had been estimated by dynamic differential scanning calorimetry, in situ Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and thermal gravimetric analyzer. The results revealed that M(acac) n of iron (Fe3+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It is reported that the acetylacetonate metal complex shows high reactivity for both epoxy and benzoxazine, as well as the remarkable tolerance to moisture which is easy to store and transport in practical use. [33,34] Figure 1c shows the nonisothermal DSC curves and isothermal gelation time at 175 °C of EDB(5/1.5/5) with different Fe(acac) 3 content. Clearly, the two exothermic peaks both move toward low temperatures, and the gelation time decreases significantly, as increasing the Fe(acac) 3 content.…”
Section: Curing Behavior Of Resin Blendsmentioning
confidence: 99%
“…It is reported that the acetylacetonate metal complex shows high reactivity for both epoxy and benzoxazine, as well as the remarkable tolerance to moisture which is easy to store and transport in practical use. [33,34] Figure 1c shows the nonisothermal DSC curves and isothermal gelation time at 175 °C of EDB(5/1.5/5) with different Fe(acac) 3 content. Clearly, the two exothermic peaks both move toward low temperatures, and the gelation time decreases significantly, as increasing the Fe(acac) 3 content.…”
Section: Curing Behavior Of Resin Blendsmentioning
confidence: 99%
“…Many substances can serve as BZ catalysts, which can be divided into acidic catalysts and alkaline catalysts based on their acidity and alkalinity. Acid catalysts include organic acids and Lewis acids, while alkaline catalysts consist of imidazole and amine compounds [ 32 , 33 ]. These catalysts can promote the cleavage of the CH 2 -O bond on the oxazine ring, shorten the curing temperature, and reduce the curing reaction time.…”
Section: Introductionmentioning
confidence: 99%